2015
DOI: 10.1016/j.ejor.2015.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Second order conic approximation for disassembly line design with joint probabilistic constraints

Abstract: a b s t r a c tA problem of profit oriented disassembly line design and balancing with possible partial disassembly and presence of hazardous parts is studied. The objective is to design a production line providing a maximal revenue with balanced workload. Task times are assumed to be random variables with known normal probability distributions. The cycle time constraints are to be jointly satisfied with at least a predetermined probability level. An AND/OR graph is used to model the precedence relationships a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(23 citation statements)
references
References 79 publications
0
23
0
Order By: Relevance
“…Task processing times: The disassembly task processing times are the most common uncertain parameter considered in DLB models. While , Özceylan and Paksoy (2014c), Kalayci et al (2015b), Seidi and Saghari (2016) and Zhang et al (2017) assumed fuzzy task processing time; the disassembly task times are assumed to be independent random variables with known and normal probability distributions by Kekre et al (2003), Ranky et al (2003), Gupta (2004, 2005), Agrawal and Tiwari (2008), Karadağ and Türkbey (2013), Bentaha et al (2013aBentaha et al ( , 2013bBentaha et al ( , 2013cBentaha et al ( , 2013dBentaha et al ( , 2013e, 2014aBentaha et al ( , 2014bBentaha et al ( , 2014cBentaha et al ( , 2014dBentaha et al ( , 2014e, 2015aBentaha et al ( , 2015b A general summary of uncertainty issues in existing DLB studies is given in Table 4. As can be seen from Table 4, all factors except task failures are considered fuzzy, and the task processing time is the most frequently studied uncertain factor handled as stochastic.…”
Section: Performance Measures Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Task processing times: The disassembly task processing times are the most common uncertain parameter considered in DLB models. While , Özceylan and Paksoy (2014c), Kalayci et al (2015b), Seidi and Saghari (2016) and Zhang et al (2017) assumed fuzzy task processing time; the disassembly task times are assumed to be independent random variables with known and normal probability distributions by Kekre et al (2003), Ranky et al (2003), Gupta (2004, 2005), Agrawal and Tiwari (2008), Karadağ and Türkbey (2013), Bentaha et al (2013aBentaha et al ( , 2013bBentaha et al ( , 2013cBentaha et al ( , 2013dBentaha et al ( , 2013e, 2014aBentaha et al ( , 2014bBentaha et al ( , 2014cBentaha et al ( , 2014dBentaha et al ( , 2014e, 2015aBentaha et al ( , 2015b A general summary of uncertainty issues in existing DLB studies is given in Table 4. As can be seen from Table 4, all factors except task failures are considered fuzzy, and the task processing time is the most frequently studied uncertain factor handled as stochastic.…”
Section: Performance Measures Studiesmentioning
confidence: 99%
“…They allow partial disassembly and simultaneously determine the disassembly level (which parts to release through which tasks), the number of stations and the cycle time along with the assignment of the tasks to the stations. Later on, partial disassembly is handled by Altekin and Akkan (2012), Bentaha et al (2013bBentaha et al ( , 2013cBentaha et al ( , 2013aBentaha et al ( , 2014aBentaha et al ( , 2014bBentaha et al ( , 2014e, 2014dBentaha et al ( , 2015b, Habibi et al (2014); Kalaycılar, Azizoğlu, and Yeralan (2016), Altekin, Bayındır, and Gümüşkaya (2016), and Ren et al (2017). However, considering partial and complete disassembly simultaneously in DLB is still lacking.…”
Section: Disassembly Levels and Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…One obvious difference between the converging assembly lines and disassembly lines is the divergence where End of Life (EOL) products are separated into their constituent components. However, in disassembly lines, quality, quantity, and reliability of parts and subassemblies are not considered as in an assembly line (Bentaha et al 2015a). Disassembly could be a partial process as it could be left incomplete because of technical and economic factors.…”
Section: Design For Assembly and Disassemblymentioning
confidence: 99%
“…This assumption was not justified and might encounter difficulty in application to planning real-world RES problems. Besides, some studies for JCP problems indicated that each marginal probability level should be satisfied with the assumption that 12 p p p + = [53,54].…”
Section: Comparison With the Conventional Jcpmentioning
confidence: 99%